2003
DOI: 10.1128/jcm.41.6.2341-2347.2003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Secondary Type III Secretion System Locus Found in Enterohemorrhagic Escherichia coli O157:H7 Isolates among Shiga Toxin-Producing E. coli Strains

Abstract: The ability of the complete genome sequence of enterohemorrhagic Escherichia coli O157 led to the identification of a 17-kb chromosomal region which contained a type III secretion system gene cluster at min 64.5. This locus contains open reading frames whose amino acid sequences show high degrees of similarity with those of proteins that make up the type III secretion apparatus, which is encoded by the inv-spa-prg locus on a Salmonella SPI-1 pathogenicity island. This locus was designated ETT2 (E. coli type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 22 publications
1
51
1
Order By: Relevance
“…Furthermore, they imply that the essential difference between EHEC and K-12 at this locus is a deletion in K-12 rather than an insertion into the EHEC genome, as claimed by Makino et al (35), and that the originally commensal and now laboratory- …”
Section: Vol 186 2004 Comparative Genomics Of Ett2 Gene Clusters 3549mentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, they imply that the essential difference between EHEC and K-12 at this locus is a deletion in K-12 rather than an insertion into the EHEC genome, as claimed by Makino et al (35), and that the originally commensal and now laboratory- …”
Section: Vol 186 2004 Comparative Genomics Of Ett2 Gene Clusters 3549mentioning
confidence: 98%
“…Three recent studies have shown that the ETT2 gene cluster is found in some pathogenic strains of E. coli in addition to O157:H7 (23,35,40). However, these studies failed to agree on the boundaries of the cluster, were limited in terms of the phylogenetic diversity of the strains they sampled (leading to the erroneous conclusion that ETT2 is largely absent from nonpathogenic strains), and did not describe any ETT2-associated chaperone or translocator genes.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…New pandemic strains of this pathogen are emerging throughout the world (1). Sequencing of the V. para genome identified two pathogenicity islands encoding type III secretion systems, TTSS1 and TTSS2, the latter associated with virulent, clinical isolates of V. para (2). Iida and colleagues (3,4) have demonstrated that the TTSS on chromosome one (TTSS1) is linked to cytotoxicity in infected tissue culture cells, whereas the TTSS on chromosome two (TTSS2) is associated with enterotoxicity in the rabbit ileal loop model.…”
mentioning
confidence: 99%